Metallic glass flake, preparation method thereof and application of metallic glass flake in heavy anti-corrosion coating
By using metal glass flakes with ingredients Fe, Cr, P, MA and MB, the problem of poor corrosion resistance in acidic or alkaline environments is solved, and heavy corrosion-proof coatings with high wear resistance, adhesion and corrosion resistance are achieved, and self-healing performance is given.
Patent Information
- Application Number
- CN202411546240.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-01
- Publication Date
- 2025-02-25
AI Technical Summary
The zinc powder commonly used in existing heavy corrosion protection coatings has poor anti-corrosion effect in acidic or alkaline environments, and may lead to environmental pollution during service, and conventional scale fillers have limited effect on the lifting of the coating.
Metal glass flakes are used as anti-corrosion filler, and their components include Fe, Cr, P, MA and MB, with irregular shape edge and high diameter and thickness ratio (≥3). By regulating the composition and structural characteristics, the wear resistance, adhesion and corrosion resistance of the paint are improved.
It significantly improves the corrosion resistance of heavy corrosion-resistant coatings in complex and harsh corrosion environments, enhances the strength and toughness of the coating, and gives self-repair performance, expanding the comprehensive application scenarios of coatings.
Smart Images

Figure CN119501078A_ABST
Abstract
Description
Technical Field
[0001] The invention relates to the technical field of amorphous alloys, and in particular to a metallic glass flake and a preparation method thereof and application thereof in heavy-duty anti-corrosion coatings. Background Art
[0002] Heavy-duty anti-corrosion coating is a coating with excellent anti-corrosion performance. It has a better protection period than conventional anti-corrosion coatings and is suitable for relatively harsh corrosive environments such as acid, alkali, salt and solvent media. It is widely used in ships, containers, bridges, petrochemicals, electric power, railway engineering, building steel structures and other fields. Heavy-duty anti-corrosion coatings are mainly composed of film-forming materials, anti-corrosion fillers and additives. Generally, water-based resins with specific cross-linking (such as epoxy resins or phenolic epoxy resins) are used as film-forming materials, and anti-corrosion fillers often use zinc powder, which is used as a sacrificial anode to allow the corrosive medium to obtain electrons and protect the base material. However, since zinc powder has a poor anti-corrosion effect in acidic or alkaline environments, and zinc ions will be formed during the service of anti-corrosion coatings, causing marine or soil pollution, people began to use flake fillers (mica flakes, glass flakes, stainless steel flakes, graphite flakes, etc.) instead of zinc powder as anti-corrosion fillers. Compared with zinc powder, the flaky fillers are distributed in the coating in a parallel, overlapping and cross-arranged manner, which can form a barrier that effectively prevents the medium from invading, and produce a maze effect to force the medium to intrude in a circuitous way, making it difficult for the medium to contact the substrate, thereby extending the service life of the protected base material. However, the above conventional flaky fillers have limited effect on heavy-duty anti-corrosion coatings and need to be improved. Summary of the invention
[0003] The purpose of the present invention is to overcome the shortcomings of the prior art and provide a metallic glass flake and a preparation method thereof and an application thereof in a heavy-duty anti-corrosion coating.
[0004] To achieve the above object, the technical solution adopted by the present invention is:
[0005] In a first aspect, the present invention provides a metallic glass flake, which is a flaky amorphous alloy having irregular edges, and the composition thereof includes Fe, Cr, P, MA and MB;
[0006] The MA is at least one of B, C, and Si; the MB is at least one of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Td, Dy, Ho, Er, Tm, Yb, and Lu;
[0007] The molar percentage of Fe in the metallic glass flakes is 40% to 80%, the molar percentage of Cr is 1% to 40%, the molar percentage of P is 1% to 20%, the molar percentage of MA is 1% to 10%, and the molar percentage of MB is 0% to 5% (the sum of the molar percentages of Fe, Cr, P, MA and MB is equal to 100%); the diameter-to-thickness ratio of the metallic glass flakes is ≥3.
[0008] The present invention forms specific metallic glass flakes by regulating the composition of metallic glass flakes (combining P with Fe, Cr and MA) and its diameter-to-thickness ratio (≥3) and edge shape (the edge has an irregular shape). The metallic glass flakes not only have high strength, which can improve the wear resistance of heavy-duty anti-corrosion coatings; they also have low modulus, which can improve the adhesion of heavy-duty anti-corrosion coatings; at the same time, the irregular edges can also enhance its bonding with the resin, thereby improving the strength and toughness of the heavy-duty anti-corrosion coatings; in addition, it is easier to form a maze structure to effectively prevent the intrusion of media, and coupled with its own excellent resistance to acid and alkaline corrosion, the corrosion resistance of heavy-duty anti-corrosion coatings in complex and harsh corrosive environments is significantly improved, fully expanding the comprehensive application scenarios of heavy-duty anti-corrosion coatings.
[0009] In addition, the appropriate content of P element in the metallic glass flakes of the present invention can play a corrosion inhibition role, thereby giving the heavy-duty anti-corrosion coating a certain self-repairing property. Even when the anti-corrosion coating formed by the heavy-duty anti-corrosion coating is micro-damaged, it can produce a complex with the corrosion products of the substrate to form a new protective film, thereby greatly improving the overall anti-corrosion performance.
[0010] It should also be noted that the aspect ratio of the above-mentioned metallic glass flakes refers to the ratio of the particle size of the metallic glass flakes to its thickness, aspect ratio = particle size D95 / average thickness, where the units of particle size D95 and average thickness are both μm.
[0011] Optionally, the molar percentage of Fe in the metallic glass flakes can be any one of 40%, 45%, 50%, 55%, 60%, 65%, 70%, 75%, 80% or any two of the range values; the molar percentage of Cr can be any one of 1%, 3%, 5%, 7%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or any two of the range values; the molar percentage of P can be 1%, 2%, 4%, 5%, 6%, 7%, 8%, 9%, 10%, 15%, 20%, 25%, 30%, 35%, 40% or any two of the range values; , 6%, 8%, 10%, 12%, 14%, 16%, 18%, 20% or any two of the range values; the molar percentage of MA can be specifically 1%, 2%, 4%, 6%, 8%, 10% or any two of the range values; the molar percentage of MB can be specifically 0.1%, 0.5%, 1%, 1.5%, 2%, 2.5%, 3%, 3.5%, 4%, 4.5%, 5% or any two of the range values.
[0012] As a preferred embodiment of the metallic glass flakes of the present invention, the diameter-to-thickness ratio of the metallic glass flakes is 3 to 400. Optionally, the diameter-to-thickness ratio of the metallic glass flakes can be any one of 3, 5, 7, 10, 15, 20, 25, 30, 35, 40, 45, 50, 55, 60, 65, 70, 75, 80, 85, 90, 95, 100, 150, 200, 300, 400 or any two of the range values. Studies have found that the diameter-to-thickness ratio of metallic glass flakes affects the anti-corrosion performance of heavy-duty anti-corrosion coatings. Compared with metallic glass flakes with a small diameter-to-thickness ratio, metallic glass flakes with a large thickness-to-diameter ratio can form more flake layers in the coating dry film, thereby increasing the movement path of the corrosive medium to the substrate, thereby improving the anti-corrosion performance of the heavy-duty anti-corrosion coating.
[0013] As a preferred embodiment of the metallic glass flakes of the present invention, the average thickness of the metallic glass flakes is 0.8 to 30 μm; and / or the particle size D95 of the metallic glass flakes is 30 to 320 μm. Optionally, the average thickness of the metallic glass flakes can be any one of 0.8 μm, 1 μm, 3 μm, 5 μm, 7 μm, 9 μm, 12 μm, 14 μm, 16 μm, 18 μm, 20 μm, 22 μm, 24 μm, 26 μm, 28 μm, 30 μm, or any two of the range values; the particle size D95 of the metallic glass flakes can be any one of 30 μm, 50 μm, 70 μm, 90 μm, 110 μm, 150 μm, 200 μm, 250 μm, 280 μm, 320 μm, or any two of the range values. The average thickness and particle size of the metallic glass flakes can be measured by a scanning electron microscope (eg, model JEOL-IT800).
[0014] As a preferred embodiment of the metallic glass flakes of the present invention, the molar percentage of Fe in the metallic glass flakes is 70% to 75%, the molar percentage of Cr is 8% to 11%, the molar percentage of P is 8% to 10%, the molar percentage of MA is 6% to 10%, and the molar percentage of MB is 1% to 2%.
[0015] Preferably, the molar percentages of Fe, Cr, P, MA and MB in the metallic glass flakes are 70%, 11%, 10%, 7% and 2%, respectively; or the molar percentages of Fe, Cr, P, MA and MB in the metallic glass flakes are 72%, 8%, 9%, 10% and 1%, respectively; or the molar percentages of Fe, Cr, P, MA and MB in the metallic glass flakes are 75%, 10%, 8%, 6% and 1%, respectively; or the molar percentages of Fe, Cr, P, MA and MB in the metallic glass flakes are 75%, 10%, 8%, 7% and 0%, respectively.
[0016] In a second aspect, the present invention provides a method for preparing the above-mentioned metallic glass flakes, which specifically comprises the following steps:
[0017] S1, spraying the alloy melt onto the surface of a metal flake forming plate having a semicircular cross section through an air nozzle of an atomizing device, and cooling to obtain metal flake powder;
[0018] S2. Ball-milling the metal flake powder in S1 to obtain metallic glass flakes.
[0019] Optionally, step S1 in the above preparation method can be specifically as follows: placing the alloy ingot into a high-frequency induction gas atomization device, the diameter of the metal liquid outflow outlet of the high-frequency induction furnace is 1 to 3 mm, the temperature is 1300 to 1500°C, and the metal liquid is made to flow out by self-weight or pressurization, with a flow rate of 1 to 20 mL / s; the diameter of the atomizing gas nozzle is 2 to 6 mm, and the gas pressure is 6 to 10 MPa; the distance between the gas nozzle and the metal liquid is 5 to 25 mm, and the angle between the gas ejection direction and the metal liquid is 30 to 60°; the gas is Ar, N2 or other inert gases.
[0020] A circulating water-cooled arc-shaped ceramic plate is placed directly in front of the air nozzle as a metal flake forming plate. The cooling water temperature is not higher than 15°C. The cross-section of the forming plate is semicircular with a radius of 50 to 80 mm. The forming plate is placed vertically opposite the air nozzle, and the metal liquid outflow outlet is located at the center of the cross-section of the forming plate. Furthermore, the forming plate is inclined away from the metal liquid with the center of the bottom cross-section as the base point, and the inclination angle is less than 30°, and powder is collected at the bottom of the forming plate.
[0021] The alloy ingot can be prepared by the following method: placing the raw materials of the alloy into a non-consumable vacuum arc melting furnace, evacuating the furnace to a vacuum of 1×10 -2Pa or less, the heating temperature is 1000-2500℃, the smelting time is 1-30min, and the raw materials are smelted evenly for 1-5 times under the smelting conditions. The alloy ingot is taken out after cooling in the furnace to ensure that the mass loss of the alloy ingot before and after smelting is less than 0.1wt%.
[0022] As a preferred embodiment of the method for preparing the metallic glass flakes of the present invention, the ball milling speed of the ball milling treatment in S2 is 200-300 r / min, and the ball milling time is 1-5 h. Optionally, the ball milling time can be any one of 1 h, 1.5 h, 2 h, 2.5 h, 3 h, 3.5 h, 4.5 h, 5 h, or any two of the range values. Studies have found that when the ball milling time is 1 to 5 h, it can not only avoid the presence of a large number of large-sized particles to improve the uniformity of the particle size of the metallic glass flakes, but also effectively prevent the metallic glass flakes from agglomerating due to their small particle size.
[0023] As a preferred embodiment of the method for preparing metallic glass flakes of the present invention, the mass ratio of the ball-milled ceramic balls to the metal powder in S2 is 50:(0.5-1.5). Optionally, the mass ratio of the ceramic balls to the metal powder can be any one of 50:0.5, 50:0.7, 50:1, 50:1.3, 50:1.5, or any two of the range values.
[0024] Optionally, the ball milling treatment specifically includes the following steps: placing the metal flake powder into a planetary ball mill, the ball-to-material mass ratio is 50:(0.5-1.5), the mass ratio of the ceramic balls of different sizes used is 1:1 (wherein the diameter of the large ceramic ball is 130 mm, and the diameter of the small ceramic ball is 20 mm). Adding an appropriate amount of anhydrous ethanol as a buffer reagent can also help to remove the powder sample, the ball milling speed is 200-300 r / min, the ball milling operation mode is one hour of rotation and ten minutes of rest, and the ball milling time is 1-5 hours to obtain irregular edge powder.
[0025] In a third aspect, the present invention provides the use of the above-mentioned metallic glass flakes in heavy-duty anti-corrosion coatings.
[0026] In a fourth aspect, the present invention provides an anti-corrosion filler for heavy-duty anti-corrosion coatings, the anti-corrosion filler comprising the above-mentioned metallic glass flakes.
[0027] In a fifth aspect, the present invention provides a heavy-duty anti-corrosion coating, which includes the above-mentioned metallic glass flakes or the above-mentioned anti-corrosion filler for heavy-duty anti-corrosion coating.
[0028] Compared with the prior art, the present invention has the following beneficial effects:
[0029] The present invention forms specific metallic glass flakes by regulating the composition of metallic glass flakes, their diameter-to-thickness ratio (≥3) and edge shape (the edge has an irregular shape). The metallic glass flakes not only have high strength, which can improve the wear resistance of heavy-duty anti-corrosion coatings; they also have low modulus, which can improve the adhesion of heavy-duty anti-corrosion coatings; at the same time, the irregular edges can also enhance their bonding with the resin, thereby improving the strength and toughness of the heavy-duty anti-corrosion coatings; in addition, it is easier to form a maze structure to effectively prevent the intrusion of media, and coupled with its own excellent resistance to acid and alkaline corrosion, the corrosion resistance of heavy-duty anti-corrosion coatings in complex and harsh corrosive environments is significantly improved, fully expanding the comprehensive application scenarios of heavy-duty anti-corrosion coatings. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] Figure 1 is the SEM image of the metallic glass flakes in Examples 1, 2 and 3;
[0031] Figure 2 is the XRD pattern of the metallic glass flakes in Examples 1, 2 and 3;
[0032] Figure 3 The potentiodynamic polarization curves of the metallic glass flakes and SUS304 stainless steel in Examples 1 to 3 in 3 wt % NaCl solution are shown. DETAILED DESCRIPTION
[0033] In order to better illustrate the purpose, technical solutions and advantages of the present invention, the present invention will be further described below in conjunction with specific embodiments.
[0034] Unless otherwise specified, other materials, reagents, etc. used in the examples can be obtained from commercial sources.
[0035] Examples 1 to 4 and Comparative Examples 1 to 2
[0036] Table 1 Composition of metallic glass flakes in Examples 1 to 4 and Comparative Examples 1 to 2, their particle size D95, average thickness and thickness ratio (thickness ratio = particle size D95 / average thickness)
[0037]
[0038]
[0039] The preparation methods of the metallic glass flakes in Examples 1 to 4 and Comparative Example 1 are the same, comprising the following steps:
[0040] Step 1: Ingredients: According to the metallic glass flakes (Fe a Cr b P c MA d MB e) Weigh the raw materials Fe, Cr, P, MA and MB (total mass is 100 g).
[0041] Step 2: Alloy smelting: Place the raw materials weighed in step 1 into a non-consumable vacuum arc melting furnace and evacuate to 1×10 -2 Pa, the heating temperature is 1350℃, the smelting time is 10min, and the raw materials are smelted three times under the smelting conditions to make the raw materials smelted evenly. The alloy ingot is taken out after cooling in the furnace to ensure that the mass loss of the alloy ingot before and after smelting is less than 0.1wt%.
[0042] Step 3, powder atomization: put the alloy ingot prepared in step 2 into the high-frequency induction gas atomization equipment, the diameter of the metal liquid outflow outlet of the high-frequency induction furnace is 1mm, the temperature is 1280℃, and the metal liquid is made to flow out by self-weight or pressurization, with a flow rate of 5mL / s; the diameter of the atomizing gas nozzle is 3mm, and the gas pressure is 6Mpa; the distance between the gas nozzle and the metal liquid is 10mm, the angle between the gas spray direction and the metal liquid is 30°, and the gas is Ar.
[0043] Step 4. Preparation of metal flakes: Place a circulating water-cooled arc-shaped ceramic plate as a metal flake forming plate directly in front of the air nozzle. The cooling water temperature is not higher than 15°C. The cross-section of the forming plate is semicircular with a radius of 50mm. The forming plate is placed vertically facing the air nozzle. The metal liquid flow outlet is located at the center of the cross-section of the forming plate. Powder is collected at the bottom of the forming plate to obtain metal flake powder.
[0044] Step 5. Metal flake forming: The metal flake powder described in step 4 is placed in a planetary ball mill with a ball-to-material ratio of 50:1. The mass ratio of large and small ceramic balls (the diameter of the large ceramic balls is 130 mm and the diameter of the small ceramic balls is 20 mm) is 1:1. Adding an appropriate amount of anhydrous ethanol as a buffer reagent can also help to remove the powder sample. The ball mill speed is 250 r / min, and the ball mill operation mode is 1 hour per rotation and 10 minutes of rest. The ball mill time is 2 hours to obtain metallic glass flakes.
[0045] The preparation method of Example 2 is substantially the same as that of Example 1, except that no ball milling is performed (ie, step five is not performed).
[0046] Performance Testing
[0047] 1. Metallic glass flakes
[0048] 1) Morphology test
[0049] Figure 1 (a) is the metallic glass flake (Fe 70 Cr 11 P 10 C7Pr1Y1) and (b) the SEM image of the metallic glass flake (Fe72 Cr8P9B5C2Si3Ce1), (c) the SEM image of the metallic glass flake (Fe 75 Cr 10 P8B3C2Si1Lu1) SEM picture, according to Figure 1 It can be seen that the particle size distribution of the metallic glass flakes in Examples 1 to 3 is uniform, and their edges present an irregular shape.
[0050] 2) XRD test
[0051] according to Figure 2 It can be seen that the metallic glass flakes (Fe 70 Cr 11 P 10 C7Pr1Y1), the metallic glass flakes (Fe 72 Cr8P9B5C2Si3Ce1) and the metallic glass flakes (Fe 75 Cr 10 The main diffraction peaks of P8B3C2Si1Lu1) all have a steamed bun-like shape, that is, the metallic glass flakes in Examples 1, 2 and 3 are all in a typical metallic glass state; at the same time, combined with their SEM images, it is fully proved that the metallic glass flakes of the present invention are flaky amorphous alloys with irregular edges.
[0052] 3) Potentiodynamic polarization test
[0053] according to Figure 3 It can be seen that in a sodium chloride aqueous solution with a mass solubility of 3%, the metallic glass flakes (Fe 70 Cr 11 P 10 The self-corrosion potential of the metallic glass flakes (Fe 72 The self-corrosion potential of the metallic glass flakes (Fe 75 Cr 10 The self-corrosion potential of P8B3C2Si1Lu1) reaches -0.135V, which is much higher than the self-corrosion potential of 304 stainless steel (-0.277V), indicating that the metallic glass flakes of the present invention have excellent corrosion resistance.
[0054] 2. Heavy anti-corrosion coating
[0055] The metallic glass flakes and zinc powder in Examples 1 to 4 and Comparative Examples 1 to 2 are used as anti-corrosion fillers and are respectively mixed with epoxy resin (brand 3800, manufacturer Jiangsu Sanmu), titanium dioxide (brand LR108, manufacturer Longmang), dispersant (brand BYK110, manufacturer BYK Chemical), defoaming agent (brand BYKA530, manufacturer BYK Chemical) and organic solvent (n-butanol + xylene) to form component A.
[0056] Among them, the mass fraction of titanium dioxide in component A is 7%, the mass fraction of dispersant is 1%, the mass fraction of defoaming agent is 1%, the mass fraction of n-butanol is 11%, the mass fraction of xylene is 10%, and the remainder is a mixture of metallic glass flakes or zinc powder and epoxy resin; when metallic glass flakes are combined with epoxy resin, the mass fraction of metallic glass flakes in component A is 40%; when zinc powder is combined with epoxy resin, the mass fraction of zinc powder in component A is 30%.
[0057] Component A and component B (curing agent, brand LITE 3070, manufacturer Cardolite) were mixed uniformly at a mass ratio of 9:1 to obtain a heavy anti-corrosion coating with a dry film thickness of 120 μm. The following tests were then performed, and the test results are shown in Table 2.
[0058] 1) Adhesion test: According to GB / T 5210-2006 standard, the coating sample is fixed on the test equipment, and then a tensile force is applied at a constant speed until the coating is peeled off from the substrate.
[0059] 2) Impact strength: According to GB / T 1731-2020, a 1kg steel ball is dropped freely from a height, and the recoil method is used to observe whether cracking and peeling occur on the surface of the paint film.
[0060] 3) Bending resistance: According to GB / T 20624-2006 standard, different diameters of mandrels are used, and the curvature radius is 2.0mm, 2.5mm, 5.0mm and 7.5mm respectively. The painted tinplate is placed on mandrels of different diameters and the flexibility of the coating is tested by bending. The mandrel with the smallest diameter is the one that does not break the coating after bending. The number of millimeters of its diameter is the evaluation value of flexibility.
[0061] 4) Hardness test: The dried paint film is tested for hardness using a Mohs hardness tester with 5 test points, and the average value is taken.
[0062] 5) Neutral salt spray resistance test: According to GB / T1771-2007 standard, the test is carried out in a salt spray test chamber, using a 5% sodium chloride saline solution with a pH value adjusted to a neutral range (6.5-7.2) as the spray solution; the test temperature is 35°C, and the salt spray sedimentation rate is required to be 1-3mL / 80cm 2 h.
[0063] 6) Acidic salt spray test: According to GB / T1771-2007 standard, the test is carried out in a salt spray test chamber, using a 5% sodium chloride saline solution with a pH value adjusted to the acidic range (1-1.5) as the spray solution; the test temperature is 35°C, and the salt spray sedimentation rate is required to be 1-3mL / 80cm 2 h.
[0064] Table 2 Performance of the corresponding heavy anti-corrosion coatings of each embodiment, comparative example and zinc powder
[0065]
[0066] According to the data in Table 2, the adhesion of the heavy-duty anti-corrosion coatings corresponding to Examples 1 to 4 is greater than 17 MPa, reaching 17.5 to 21.8 MPa; the impact strength reaches 50 cm, the bending resistance reaches 1 mm, the Mohs hardness reaches 7, the neutral salt spray resistance reaches 5000 to 6000 h, and the acid salt spray resistance reaches 500 h, indicating that the metallic glass flakes of the present invention can give the heavy-duty anti-corrosion coating good strength and toughness, which can not only improve the adhesion of the heavy-duty anti-corrosion coating, but also improve the wear resistance of the heavy-duty anti-corrosion coating, and significantly improve the corrosion resistance of the heavy-duty anti-corrosion coating under complex and harsh corrosive environment conditions.
[0067] Finally, it should be noted that the above embodiments are only used to illustrate the technical solution of the present invention rather than to limit the scope of protection of the present invention. Although the present invention has been described in detail with reference to the preferred embodiments, those skilled in the art should understand that the technical solution of the present invention can be modified or replaced by equivalents without departing from the essence and scope of the technical solution of the present invention.
Claims
1. A metallic glass flake, characterized in that: The metallic glass flakes are flaky amorphous alloys with irregular edges, and the components thereof include Fe, Cr, P, MA and MB; The MA is at least one of B, C, and Si; the MB is at least one of Y, La, Ce, Pr, Nd, Sm, Eu, Gd, Td, Dy, Ho, Er, Tm, Yb, and Lu; The molar percentage of Fe in the metallic glass flakes is 40% to 80%, the molar percentage of Cr is 1% to 40%, the molar percentage of P is 1% to 20%, the molar percentage of MA is 1% to 10%, and the molar percentage of MB is 0% to 5%; the diameter-to-thickness ratio of the metallic glass flakes is ≥3.
2. The metallic glass flake according to claim 1, characterized in that: The diameter-to-thickness ratio of the metallic glass flakes is 3-400.
3. The metallic glass flake according to claim 1, characterized in that: The average thickness of the metallic glass flakes is 0.8 to 30 μm; and / or the particle size D95 of the metallic glass flakes is 30 to 320 μm.
4. The metallic glass flake according to claim 1, characterized in that: The molar percentage of Fe in the metallic glass flakes is 70% to 75%, the molar percentage of Cr is 8% to 11%, the molar percentage of P is 8% to 10%, the molar percentage of MA is 6% to 10%, and the molar percentage of MB is 1% to 2%.
5. The method for preparing the metallic glass flakes according to any one of claims 1 to 4, characterized in that: The following steps are involved: S1, spraying the alloy melt onto the surface of a metal flake forming plate having a semicircular cross section through an air nozzle of an atomizing device, and cooling to obtain metal flake powder; S2. Ball-milling the metal flake powder in S1 to obtain metallic glass flakes.
6. The preparation method according to claim 5, characterized in that: The ball milling speed of the ball milling treatment in S2 is 200 to 300 r / min, and the ball milling time is 1 to 5 hours.
7. The preparation method according to claim 5, characterized in that: The mass ratio of the ball-milled ceramic balls to the metal flake powder in S2 is 50:(0.5-1.5).
8. Use of the metallic glass flakes according to any one of claims 1 to 4 in heavy-duty anti-corrosion coatings.
9. An anticorrosive filler for heavy anticorrosion coatings, characterized in that: The anti-corrosion filler comprises the metallic glass flakes as described in any one of claims 1 to 4.
10. A heavy-duty anti-corrosion coating, characterized in that: The invention relates to an anticorrosive filler for heavy-duty anticorrosive coatings comprising the metallic glass flakes as described in any one of claims 1 to 4 or the anticorrosive filler as described in claim 9.